Porous structure of natural and modified clinoptilolites - Kowalczyk, Poitr; Sprynskyy, M.; Terzyk, A.; Lebedynet, M.; Namiesnik, J.; Buszewski, B. (Elsevier, 2005)
The evaluation of the pore-size distribution (PSD) of natural and modified mesoporous zeolites, i.e., clinoptilolites is presented.We demonstrate the SEM results showing that the pores of fracture-type from 25–50 nm to 100 nm in size between clinoptilolite grains, as well as pores between crystal aggregates up to 500 nm in size are present in the studied material. The detailed distribution of pore sizes and tortuosity factor of the above-mentioned materials are determined from the adsorption–desorption isotherms of nitrogen measured volumetrically at 77 K. To obtain the reliable pore size distribution (PSD) of the above-mentioned materials both adsorption and desorption branches of the experimental hysteresis loop are described simultaneously by recently developed corrugated pore structure model (CPSM) of Androutsopoulos and Salmas. Evaluated pore size distributions are characterized by well-defined smooth peaks placed in the region of the mesoporosity.Moreover, the mean pore diameter calculated from the classical static measurement of nitrogen adsorption at 77 K correspond very well to the pore diameters from SEM, showing the applicability of the CPSM for characterization of the porosity of natural zeolites. We conclude that classical static adsorption measurements combined with the proper modeling of the capillary condensation/evaporation phenomena are a powerful method which can be applied for pore structure characterization of natural and modified clinoptilolites.